Training on the utilization of artificial intelligence (AI) in project-based learning to support the implementation of deep learning for Indonesian language teachers - Ari Kusmiatun; Kastam Syamsi; Fitria Wiyarti Nindyaningrum; Mia Awaliyah; Fathul Hidayati; Denny Indria Ferawati (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2025)
This training aims to train Indonesian language teachers in using AI actively, creatively, and innovatively as artificial intelligence-based learning media in the era of learning with a deep learning approach. The activity was attended by 40 Indonesian language teachers from MTs and MA in Bantul Regency. This program is in collaboration with the MGMP Bahasa Indonesia MTs, Bantul Regency and supported by the Department of Education, Department of Religious Affairs, Bantul Regency. The training activity was held on Tuesday, May 27, 2025, offline at MAN 3 Bantul, followed by assignments and mentoring, then met again online on June 16, 2025. . The output of this activity is a learning design created by participants by incorporating AI elements integrated into project-based learning. In addition, the results of the satisfaction evaluation showed that participants considered this activity very beneficial for them, especially increasing insight and making language learning more interesting and enjoyable.